Physiological phimosis-the tincture of time - Ghosh, Soumyodhriti; Mujalde, Vikram Singh; Shukla, Ramendra; Gupta, Shilpi; Ali, Mushahid (International Journal of Research in Medical Sciences, 2017)
Background: Phimosis is one of the commonest presentations in the pediatric surgery outdoor. The main concern has been over avoidance of surgery in physiological phimosis. Different protocols have been proposed from time to time. Methods: An observational study was carried out in the pediatric surgery outdoor of SMS Medical College Jaipur, Rajasthan, India in 40 children aged 5 years or above who were treated for physiological phimosis by non-operative methods at some stage. Results: Ninety percent of the patients had resolution of phimosis by conservative means. The remaining patients were having difficulty in retraction, but no complications were identified in any patient. Conclusions: Phimosis is physiological and management should be restricted to reassurance in all cases that have no evidence of scarring or associated pathologies.